Method for efficiently degrading perfluorinated compounds in sludge through smoldering

By using modified graphene oxide and nanomica microparticles in sludge, combined with smelting technology, the problem of perfluoro compound treatment in high-water sludge is solved, and efficient degradation and simplification of the process is achieved. , reduces energy consumption and is suitable for industrial applications.

CN119118467AActive Publication Date: 2024-12-13GUANGDONG POLYTECHNIC OF ENVIRONMENTAL PROTECTION ENG +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411572742.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2024-12-13
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently treat perfluoro compounds in sludge with high moisture content, and the existing methods require pre-dehydration treatment, which is costly and not suitable for large-scale treatment, and the thermal conductivity during the smoldering process is too low, making it difficult to achieve self-sustaining combustion.

Method used

A solid porous medium that can transfer heat and store energy, and by modifying graphene oxide and nanomica particles, combined with polymers, aminated solid porous medium is prepared for mixing with highly water-containing sludge, using smoldering technology in It provides a small amount of external heat and achieves self-sustaining combustion, destroying the C-F bond of perfluoro compounds.

Benefits of technology

It has achieved efficient degradation of the C-F bond of perfluoro compounds in sludge, with a degradation rate of more than 90%, simplified the treatment process, reduced energy consumption, is suitable for industrial applications, and avoided secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118467A_ABST
    Figure CN119118467A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of environmental protection and pollutant treatment, and particularly relates to a method for promoting biodegradation of organic fluorine compounds in sludge. On the basis of a smoldering technology, the smoldering efficiency is improved by utilizing the solid porous medium, a large amount of perfluorinated compound pollutants in the sludge are adsorbed into the solid porous medium, and the heat transfer and energy storage type aminated solid porous medium grafted with amido can be used for providing continuous heat and also can be used for adsorbing the perfluorinated compound pollutants in the sludge. The smoldering self-sustaining time is long due to the synergistic effect, perfluorinated compounds are directionally and selectively adsorbed, fluorocarbon bonds of the perfluorinated compounds are broken, and the defluorination rate of the perfluorinated compounds is 90% or above. According to the method, dehydration treatment on the sludge is not needed, required equipment is simple, automatic operation is easy to realize, and the low-calorific-value perfluorinated-compound-containing high-water-content sludge can also be efficiently degraded by utilizing a smoldering method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of environmental protection and pollutant treatment, and specifically relates to the field of sludge treatment, and in particular to a method for promoting efficient degradation of perfluorinated compounds in sludge. Background Art

[0002] Perfluorinated compounds (PFCs) are widely used as surfactants in pesticides, cosmetics, adhesives, greases and lubricants, etc. Currently, PFCs can be detected in surface water, groundwater, sediments, sludge, soil, organisms at all trophic levels of the food chain and in the human body worldwide.

[0003] Fluorine is a very subversive substance, which makes the CF bond highly polar. The CF bond is the strongest bond among all known covalent bonds, with a bond energy of about 460KJ / mol. In perfluorinated compounds, the three unpaired electrons of the fluoride ion can form a protective shell, so perfluorinated compounds are very stable, and the CF bond can even remain stable in 100% boiling sulfuric acid. Due to the hydrophobicity, high affinity for organic matter and difficult degradation of PFCs, PFCs entering the sewage treatment system are easily adsorbed and accumulated in the sludge. They are a type of organic pollutant in the sludge that is extremely difficult to degrade and has a huge toxic effect. On the other hand, my country's sludge production is huge, and the water content is as high as 80%.

[0004] At present, the use of adsorbents (such as granular or powdered activated carbon) in aqueous media seems to be the most common and effective treatment technology. The adsorbent removes and concentrates PFCs from the aqueous medium for subsequent treatment. However, this treatment technology is limited to aqueous media and is not suitable for sludge or sediments that may be affected by PFCs. At present, the main methods for harmlessly treating fluorine-containing sludge are landfill, incineration, and resource utilization. Moreover, among the various sludge disposal methods, the high water content of the sludge is a major problem. Among the various existing reduction and resource utilization disposal methods, the sludge needs to be pre-dehydrated or specially dried. For example, the sludge is used in cement batching after the water content is reduced to below 40% by a special dehydration device, which makes the sludge treatment process complicated, energy-intensive, small in processing volume, and high in processing cost.

[0005] A Chinese patent with publication number CN104496141B discloses a method for promoting the biodegradation of perfluorinated compounds in sludge, which is based on the microbial anaerobic fermentation treatment technology of sludge and bottom sludge, and achieves the purpose of degrading perfluorinated compounds in the process of microbial anaerobic fermentation by treating sludge and bottom sludge. However, this method is time-consuming, the degradation rate is not easy to control, and it is not suitable for treating a large amount of sludge.

[0006] Therefore, people are increasingly looking for a method for harmless disposal and resource utilization that does not require prior dehydration or special drying treatment of wet sludge, has no special requirements for the upper limit of sludge moisture content, has a large processing volume, and has no secondary pollution. In addition, people are looking for a method and system for reducing or degrading perfluorinated compounds with high destruction temperatures in solid porous media at a lower cost and in a simpler way.

[0007] Smoldering treatment is a new direct combustion treatment technology for organic solid waste with high water content and low calorific value. Organic solid waste that cannot be directly and independently self-sustainingly burned in conventional combustion devices can be mixed with porous media fillers and then, through smoldering technology, be able to achieve independent and self-sustaining combustion by forced air supply with a small amount of external heat. Therefore, how to use the smoldering treatment system in combination with porous media fillers to achieve efficient degradation of fluorine-containing sludge is currently a hot topic and difficulty in research. Summary of the invention

[0008] In order to overcome the shortcomings and deficiencies in the prior art, the primary purpose of the present invention is to provide a method for efficiently smoldering degradation of perfluorinated compounds in sludge. This method utilizes a solid porous medium that can transfer heat and store energy. Through the smoldering technology, independent self-sustaining combustion can be achieved by forced air supply under the condition of providing a small amount of external heat, thereby achieving efficient degradation of fluorine-containing sludge.

[0009] Firstly, a smoldering treatment method for high-water sludge containing perfluorinated compounds is provided, wherein the high-water sludge containing perfluorinated compounds is mixed with a small amount of auxiliary fuel and a large amount of solid porous medium filler to achieve the modification of low calorific value fluorinated sludge, so that the low calorific value fluorinated sludge can also be treated by the smoldering process, expanding the treatment method of high-water sludge containing perfluorinated compounds, and the treatment method is simple and economical. The sludge is high-water sludge containing perfluorinated compounds, with a water content of up to 80%, and the content of perfluorinated compounds is 100 to 300 micrograms per kilogram of dry weight of sludge. The auxiliary fuel is one or a mixture of sawdust, rice husks, charcoal particles or crushed straw.

[0010] The purpose of the present invention is to provide a solid porous medium filler to solve one or more technical problems existing in the prior art and at least provide a beneficial choice or create conditions. The solid porous medium filler is a solid porous medium capable of heat transfer and energy storage, and is an aminated solid porous medium grafted with amine groups for heat transfer and energy storage. In order to solve the problem that the thermal conductivity of sludge is too low during the smoldering process, and a large amount of heat is required from the outside to sustain combustion, and because the sludge has a high water content, the energy storage is too low during the smoldering process, and it cannot independently sustain combustion, we have prepared a solid porous medium that can transfer heat and store energy. It can not only improve the heat conduction during the smoldering process and improve the smoldering efficiency, but also promote the problem of sludge continuing to maintain energy in the entire smoldering system, so that after a small amount of energy is provided from the outside, the entire smoldering system can achieve uniform self-sustaining combustion through the solid porous medium that transfers heat and stores energy. The preparation method of the solid porous medium that can transfer heat and store energy is specifically as follows: S001, taking natural mica particles and heating them to 600°C for 1 hour to obtain activated mica particles, soaking the activated mica particles in a concentrated hydrochloric acid solution and stirring for 2 to 3 hours, filtering, washing with 70°C deionized water until neutral, and evaporating at 70°C, adding sodium dodecyl sulfate, heating to 80°C, reacting for 2 to 3 hours, centrifuging the obtained solid, washing with 80°C deionized water, evaporating at 80°C and grinding to obtain nano mica particles with enlarged micropores; wherein the mass ratio of activated mica flakes to sodium dodecyl sulfate is 2:1; S002, high molecular weight polyvinyl alcohol and deionized water are stirred and heated at 100°C for 80 to 120 minutes until they are completely dissolved to obtain a polyvinyl alcohol solution, wherein the concentration of the polyvinyl alcohol solution is 3 to 6%; S003, adding graphene oxide and nano-mica particles to the polyvinyl alcohol solution, stirring for 30 to 50 minutes to evenly disperse the solid particles in the polyvinyl alcohol solution, fully reacting at 80° C. for 4 hours, drying the product at 20° C., crushing and grinding to obtain a solid porous medium capable of heat transfer and energy storage; The mass ratio of graphene oxide, nano-mica particles and polyvinyl alcohol is 5-8:5-10:3-6; The solid porous medium capable of heat transfer and energy storage and the fluorine-containing sludge with high water content were mixed evenly at a mass ratio of 5:100-150, and then auxiliary fuel was added and placed in a smoldering system for treatment. We found that after adding this solid porous medium capable of heat transfer and energy storage, the smoldering system required significantly less external energy input. However, after the sludge was treated, we found that the degradation rate of perfluorinated compounds in the sludge was only about 50%. The main reason for this is that there is a large amount of graphene oxide in the solid porous medium capable of heat transfer and energy storage, and graphene oxide is easy to agglomerate in the smoldering system, so Solid porous media can only form smoldering self-sustaining combustion around themselves. This self-sustaining is unevenly dispersed and has no directional selectivity for perfluorinated compounds, which also makes it impossible to effectively degrade all perfluorinated compounds. Although the smoldering system has its own stirring system, the viscosity of the sludge itself makes the stirring efficiency low and there are dead corners in the stirring. It is difficult for the entire smoldering system to be in a completely uniform state. Especially when the external energy supply stops, stirring will not only cause energy loss, but also interfere with the accumulation of energy in the smoldering process, and cannot reach the high temperature required to destroy perfluorinated compounds.

[0011] Therefore, we further modified the graphene oxide so that it can be evenly dispersed in organic solutions or water, and has directional selectivity for perfluorinated compounds. Then the matrix wrapped by it is improved, and finally it is prepared into an aminated solid porous medium that can transfer heat and store energy. Among them, the polymer solution is not only the matrix of the solid porous medium, but also the main heat source for smoldering, which can assist the auxiliary fuel to make the entire smoldering process break through the high temperature of 800°C. The preparation method of the aminated solid porous medium with heat transfer and energy storage is specifically as follows: S101, adding hyperbranched polyamide-amine to an aqueous solution of graphene oxide, adjusting the solution to be alkaline with a 0.05% mass concentration of NaOH solution, then adding 1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, stirring and reacting at 60-80° C. for 10-15 hours, centrifuging, washing with water, and drying to obtain graphene oxide grafted with hyperbranched polyamide-amine; The mass ratio of graphene oxide, 1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and hyperbranched polyamide-amine is 1:1:3-5; Under alkaline catalytic conditions, the amine groups in the hyperbranched polyamide-amine and the epoxy groups on the graphene oxide undergo a ring-opening reaction to obtain amine-modified graphene oxide, which can be stably dispersed in water or organic solvents. Graphene oxide is a carbon skeleton material with a two-dimensional nanostructure. It can not only adsorb ions by itself, but also is a good carrier for other substances. Hyperbranched polyamide-amine is a non-toxic, biocompatible dendritic macromolecule with a large number of amino groups at the end, making it an ideal modifier. The surface of modified graphene oxide is enriched with positively charged amino groups, which makes it easier to directional adsorb negatively charged perfluorinated compounds. S102, high molecular weight polyether ether alcohol and N, N-dimethylamide are stirred and heated at 80°C for 80 to 120 minutes until they are completely dissolved to form a transparent liquid; polylactic acid and ethanol are dissolved in a mass ratio of 1:2 and then added into the transparent liquid to finally obtain a polymer solution; the mass ratio of polyether ether alcohol and N, N-dimethylamide is 1:1; the mass ratio of polyether ether alcohol and polylactic acid is 1:1 to 2; S103, adding graphene oxide grafted with hyperbranched polyamide-amine and nano-mica particles to the polymer solution, stirring for 30 to 50 minutes to evenly disperse the solid particles in the composite polymer solution, fully reacting at 60° C. for 4 hours, drying the product at 20° C., crushing and grinding to obtain an aminated solid porous medium capable of heat transfer and energy storage; the mass ratio of graphene oxide of hyperbranched polyamide-amine, nano-mica particles and polyetheretheralcohol is 5 to 8:5 to 10:10 to 20; The porous material not only provides a reaction area for smoldering, but also ensures that sufficient oxygen diffuses to the fuel surface for oxidation exothermic reaction. Compared with flaming combustion, smoldering propagates under oxygen-limited conditions, so the oxidation reaction rate is slower, and the corresponding reaction temperature and reaction rate are lower. However, this characteristic makes smoldering more stable, and the continuously released heat can be continuously absorbed and stored by mica. When the outside world cannot continue to increase energy or the outside world's ability cannot be transmitted, the polymer in the composite polymer solution can release a large amount of heat under high temperature, and the energy stored in mica can also be released continuously, so that smoldering can use the energy of the fuel itself to achieve self-sustaining, and can be carried out evenly and stably in the entire system, so that a large amount of heat energy is accumulated, thereby reaching a high temperature of 800°C, which plays a role in destroying perfluorinated compounds, so that the entire system can efficiently degrade perfluorinated compounds in sludge.

[0012] During the smoldering process of polyetheretheralcohol and polylactic acid, the carbon-hydrogen bond can be broken and energy can be released, thereby maintaining the combustion reaction. At the same time, polyetheretheralcohol and polylactic acid have large molecular weights and long molecular chains. Under high temperature, the solid porous medium that can transfer heat and store energy is used as the skeleton to connect the entire sludge system into a network structure, and at the same time, it provides sufficient energy to support the combustion reaction. In particular, polyetheretheralcohol can release a large amount of heat at high temperatures, which can promote the auxiliary fuel to reach a higher smoldering temperature, so that the temperature can rise to more than 800°C during smoldering, generating a high temperature sufficient to destroy perfluorinated compounds; and no toxic gases such as nitrogen and sulfur are produced during the combustion process.

[0013] Furthermore, a method for efficiently smoldering and degrading perfluorinated compounds in sludge is provided, which is specifically: S201, uniformly mixing the highly water-containing sludge containing perfluorinated compounds, the auxiliary fuel and the solid porous medium capable of heat transfer and energy storage to obtain a mixture; Wherein, the mass ratio of the highly water-containing sludge containing perfluorinated compounds, the auxiliary fuel and the solid porous medium capable of heat transfer and energy storage is 1000-1500:2-4:30-50; S202, placing the mixture into a smoldering furnace, continuously heating the mixture at 220°C to 300°C at the bottom, and supplying air from the bottom of the furnace upward at a speed of 4.0 cm / s to 6.0 cm / s, stirring the mixture until the mixture reaches 400°C to 500°C and the mixture begins to self-sustainingly smolder, stopping heating and stirring, and continuing the reaction for 18 to 24 hours to obtain a degraded sludge mixture, and testing the mixture; S203, collecting waste gas from the mixture generated during the smoldering combustion process; and finally treating the waste gas and the waste gas evaporated from the mixture.

[0014] S204, sampling and testing the degraded sludge mixture obtained in step S202. If the detected perfluoroalkane concentration does not exceed 50 ppt, the reaction is terminated. If it exceeds, continue to heat the bottom of the degraded sludge mixture in the smoldering furnace to 300°C for 1 to 3 hours, supply air from the bottom of the furnace upward at a speed of 4.0 cm / s to 6.0 cm / s, stop heating, continue the reaction for 4 to 6 hours, and retest. If it exceeds, repeat steps S204 and S203 until the detected perfluoroalkane concentration does not exceed 100 ppt.

[0015] The method can treat low calorific value fluorine-containing sludge with high water content, and solves the technical problem that the existing process cannot treat sludge with high water content. Through the aminated solid porous medium that can transfer heat and store energy, it has its own polymer combustible energy. After cutting off the external energy, it can quickly release a large amount of heat, and maintain self-sustaining combustion through the combustion of the polymer at high temperature. The graphene oxide grafted with hyperbranched polyamide-amine has a large number of amine groups on the surface, has a directional selection ability for free perfluorinated compounds in the sludge, and can destructively degrade perfluorinated compounds. The CF bond breakage rate is as high as more than 90%, achieving the effect of highly efficient degradation of perfluorinated compounds. Compared with the existing technology, it has the following beneficial effects: 1) The present invention provides a method for treating fluorine-containing sludge by smoldering, wherein high-water-content sludge is uniformly mixed with auxiliary fuel and solid porous medium to obtain a mixture, which is then put into a smoldering furnace for smoldering combustion. By using a solid porous medium capable of heat transfer and energy storage, independent self-sustaining combustion can be achieved by forced air supply under the condition of providing a small amount of external heat through smoldering technology. The combustion energy provided by a high molecular polymer at a high temperature can be wrapped in the solid porous medium capable of heat transfer and energy storage to assist the auxiliary fuel to reach a high temperature of more than 800°C, thereby destructively degrading perfluorinated compounds, and the CF bond breakage rate thereof is as high as more than 90%.

[0016] 2) The present invention modifies graphene oxide so that it can be evenly dispersed in organic solution or water and has directional selectivity for perfluorinated compounds. Then the matrix wrapped by it is improved so that it is not only the matrix of solid porous medium, but also the main heat source of smoldering. Finally, it is prepared into an aminated solid porous medium capable of heat transfer and energy storage. After the stirring is stopped during the smoldering process, it can be used as a skeleton. Under the action of high molecular polymer, the skeleton of this solid porous heat transfer material is used to connect the entire smoldering furnace to form a mesh structure. The graphene oxide grafted with hyperbranched polyamide-amine is used as a grid connection point to improve the thermal conductivity of the mixture in the smoldering furnace. Under the action of the energy released by the mica energy storage ball and the energy released by the combustion of the high molecular polymer, the heat released by itself can be quickly transferred to the surrounding sludge, which can effectively improve the thermal conductivity of the entire system, provide energy for the self-sustaining combustion of the smoldering system, and assist the auxiliary fuel to reach a high temperature that destroys the CF bond.

[0017] 3) The method for efficiently smoldering and degrading perfluorinated compounds in sludge provided by the present application has a simple process flow, convenient operation, low energy consumption, good treatment effect, and is stable and reliable. It is easy to realize industrial application and can treat low calorific value fluorine-containing sludge with high water content, solving the technical problem that the existing process cannot treat fluorine-containing sludge with high water content. The auxiliary fuel added to the low calorific value fluorine-containing sludge is agricultural and forestry waste such as sawdust and rice husk, and the amount added is very small. First, the price of agricultural and forestry waste is very cheap, and secondly, the amount of agricultural and forestry waste added is very small, which is economical. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 , Examples 2 and 3, and the degradation effect diagram of the highly efficient smoldering degradation of perfluorinated compounds in the sludge in Comparative Example 1; Figure 2 , Schematic diagram of temperature collection points in a smoldering furnace. DETAILED DESCRIPTION

[0019] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content described in the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally. Example 1 A method for efficiently smoldering and degrading perfluorinated compounds in sludge, firstly, preparing a solid porous medium capable of heat transfer and energy storage, specifically: Take 20 parts of natural mica particles and heat them to 600°C for 1 hour to obtain activated mica particles. The activated mica particles are immersed in a concentrated hydrochloric acid solution and stirred for 3 hours, then filtered, washed with 70°C deionized water until neutral, and evaporated to dryness at 70°C. 10 parts of sodium dodecyl sulfate are added thereto, and the temperature is raised to 80°C. After reacting for 3 hours, the solid obtained by centrifugation is washed with 80°C deionized water, evaporated to dryness and ground at 80°C to obtain nano mica particles with enlarged micropores. 5 parts of high molecular weight polyvinyl alcohol and 95 parts of deionized water are stirred and heated at 100°C for 80 to 120 minutes until they are completely dissolved to obtain a 5% polyvinyl alcohol solution; 5 parts of graphene oxide and 10 parts of nano-mica particles were added to 100 parts of 5% polyvinyl alcohol solution, stirred for 50 minutes to evenly disperse the solid particles in the polyvinyl alcohol solution, fully reacted at 80°C for 4 hours, and the product was dried at 20°C, crushed and ground to obtain a solid porous medium capable of heat transfer and energy storage; Furthermore, a method for efficiently smoldering and degrading perfluorinated compounds in sludge is provided, which is specifically: 1000 parts of high-water sludge containing perfluorinated compounds are uniformly mixed with 4 parts of charcoal particles and 50 parts of solid porous media capable of heat transfer and energy storage to obtain a mixture; wherein the high-water sludge contains 200 micrograms of perfluorinated compounds per 1 kilogram of dry weight of the sludge.

[0020] The mixture was placed in a smoldering furnace, and the bottom mixture was continuously heated at 220°C. At the same time, air was supplied from the bottom of the furnace upward at a speed of 4.0 cm / s and stirred until the mixture reached 420°C and began to self-sustaining smoldering combustion. The heating and stirring were stopped, and the reaction was continued for 24 hours to obtain a degraded sludge mixture. The sample was purified by solid phase extraction (SPE) and the concentrations of PFOS and PFOA were detected by high performance liquid chromatography-mass spectrometry (HPLC-MSMS).

[0021] collecting the waste gas from the mixture produced during the smoldering combustion process; and finally treating the waste gas as well as treating the evaporated waste gas in the mixture.

[0022] The concentration of perfluoroalkane compounds detected was 52 micrograms of PFOS, or 42,000 ppt, and 59 micrograms of PFOA, or 42,000 ppt, per kilogram of dry sludge. The concentration could not be further reduced by extending the reaction time.

[0023] Example 2 A method for efficiently smoldering and degrading perfluorinated compounds in sludge, firstly, preparing an aminated solid porous medium capable of heat transfer and energy storage, specifically: Take 20 parts of natural mica particles and heat them to 600°C for 1 hour to obtain activated mica particles. The activated mica particles are immersed in a concentrated hydrochloric acid solution and stirred for 3 hours, then filtered, washed with 70°C deionized water until neutral, and evaporated to dryness at 70°C. 10 parts of sodium dodecyl sulfate are added thereto, and the temperature is raised to 80°C. After reacting for 3 hours, the solid obtained by centrifugation is washed with 80°C deionized water, evaporated to dryness and ground at 80°C to obtain nano mica particles with enlarged micropores. 10 parts of graphene oxide are dispersed in 90 parts of deionized water to obtain a graphene oxide solution, and then 30 parts of hyperbranched polyamide-amine are added, and after adjusting to alkalinity with a NaOH solution with a mass concentration of 0.05%, 10 parts of 1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride are added, and the mixture is stirred and reacted at 80° C. for 15 hours, centrifuged, washed with water, and dried to obtain graphene oxide grafted with hyperbranched polyamide-amine; 10 parts of high molecular weight polyether ether alcohol and 10 parts of N, N-dimethylamide were stirred and heated at 80°C for 120 minutes until they were completely dissolved to form a transparent liquid; 10 parts of polylactic acid and 20 parts of ethanol were dissolved and then added to the transparent liquid, stirred evenly to obtain a polymer solution; Graphene oxide grafted with 5 parts of hyperbranched polyamide-amine and 10 parts of nano-mica particles were added to 50 parts of polymer solution, stirred for 50 minutes to evenly disperse the solid particles in the composite polymer solution, fully reacted at 60°C for 4 hours, and the product was dried at 20°C, crushed and ground to obtain an aminated solid porous medium capable of heat transfer and energy storage; 1000 parts of high-water sludge containing perfluorinated compounds are uniformly mixed with 4 parts of charcoal particles and 50 parts of solid porous media capable of heat transfer and energy storage to obtain a mixture; wherein the high-water sludge contains 200 micrograms of perfluorinated compounds per 1 kilogram of dry weight of the sludge.

[0024] The mixture was placed in a smoldering furnace, and the bottom mixture was continuously heated at 220°C. At the same time, air was supplied from the bottom of the furnace upward at a speed of 4.0 cm / s, and the mixture was stirred until the mixture reached 420°C and the mixture began to self-sustaining smoldering combustion. The heating and stirring were stopped, and the reaction was continued for 24 hours to obtain a degraded sludge mixture, and the mixture was tested; collecting the waste gas from the mixture produced during the smoldering combustion process; and finally treating the waste gas as well as treating the evaporated waste gas in the mixture.

[0025] The degraded sludge mixture was tested and found to contain 0.01 micrograms of PFOS, or 10 ppt, and 0.05 micrograms of PFOA, or 50 ppt.

[0026] Example 3 A method for efficiently smoldering and degrading perfluorinated compounds in sludge, firstly, preparing an aminated solid porous medium capable of heat transfer and energy storage, specifically: Take 20 parts of natural mica particles and heat them to 600°C for 1 hour to obtain activated mica particles. After soaking and stirring the activated mica particles in a concentrated hydrochloric acid solution for 2 hours, filter them, wash them with 70°C deionized water until they are neutral, evaporate them at 70°C, add 10 parts of sodium dodecyl sulfate, heat them to 80°C, react for 3 hours, centrifuge the obtained solid, wash them with 80°C deionized water, evaporate them at 80°C and grind them to obtain nano mica particles with enlarged micropores; 10 parts of graphene oxide are dispersed in 90 parts of deionized water to obtain a graphene oxide solution, and then 50 parts of hyperbranched polyamide-amine are added, and after adjusting to alkalinity with a NaOH solution with a mass concentration of 0.05%, 10 parts of 1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride are added, and the mixture is stirred and reacted at 80° C. for 15 hours, centrifuged, washed with water, and dried to obtain graphene oxide grafted with hyperbranched polyamide-amine; 20 parts of high molecular weight polyether ether alcohol and 20 parts of N, N-dimethylamide are stirred and heated at 80°C for 120 minutes until they are completely dissolved to form a transparent liquid; 10 parts of polylactic acid and 20 parts of ethanol are dissolved and then added to the transparent liquid, stirred evenly to obtain a polymer solution; Graphene oxide grafted with 8 parts of hyperbranched polyamide-amine and 8 parts of nano-mica particles were added to 50 parts of the polymer solution, stirred for 50 minutes to evenly disperse the solid particles in the composite polymer solution, fully reacted at 60°C for 4 hours, and the product was dried at 20°C, crushed and ground to obtain an aminated solid porous medium capable of heat transfer and energy storage; 1500 parts of high-water sludge containing perfluorinated compounds are uniformly mixed with 4 parts of charcoal particles and 40 parts of solid porous media capable of heat transfer and energy storage to obtain a mixture; wherein the high-water sludge contains 200 micrograms of perfluorinated compounds per 1 kilogram of dry weight of the sludge.

[0027] The mixture was placed in a smoldering furnace, and the bottom mixture was continuously heated at 220°C. At the same time, air was supplied from the bottom of the furnace upward at a speed of 4.0 cm / s, and the mixture was stirred until the mixture reached 450°C and the mixture began to self-sustaining smoldering combustion. The heating and stirring were stopped, and the reaction was continued for 24 hours to obtain a degraded sludge mixture, and the mixture was tested; collecting the waste gas from the mixture produced during the smoldering combustion process; and finally treating the waste gas as well as treating the evaporated waste gas in the mixture.

[0028] The degraded sludge mixture was tested and found to contain 0.02 micrograms of PFOS, or 20 ppt, and 0.04 micrograms of PFOA, or 40 ppt.

[0029] Example 4 A method for efficiently smoldering and degrading perfluorinated compounds in sludge, firstly, preparing an aminated solid porous medium capable of heat transfer and energy storage, specifically: Take 20 parts of natural mica particles and heat them to 600°C for 1 hour to obtain activated mica particles. After soaking and stirring the activated mica particles in a concentrated hydrochloric acid solution for 2 hours, filter them, wash them with 70°C deionized water until they are neutral, evaporate them at 70°C, add 10 parts of sodium dodecyl sulfate, heat them to 80°C, react for 3 hours, centrifuge the obtained solid, wash them with 80°C deionized water, evaporate them at 80°C and grind them to obtain nano mica particles with enlarged micropores; 10 parts of graphene oxide are dispersed in 90 parts of deionized water to obtain a graphene oxide solution, and then 40 parts of hyperbranched polyamide-amine are added, and after adjusting to alkalinity with a NaOH solution with a mass concentration of 0.05%, 10 parts of 1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride are added, and the mixture is stirred and reacted at 80° C. for 15 hours, centrifuged, washed with water, and dried to obtain graphene oxide grafted with hyperbranched polyamide-amine; 20 parts of high molecular weight polyether ether alcohol and 20 parts of N, N-dimethylamide are stirred and heated at 80°C for 120 minutes until they are completely dissolved to form a transparent liquid; 10 parts of polylactic acid and 20 parts of ethanol are dissolved and then added to the transparent liquid, stirred evenly to obtain a polymer solution; Graphene oxide grafted with 8 parts of hyperbranched polyamide-amine and 10 parts of nano-mica particles are added to 50 parts of polymer solution, stirred for 30 to 50 minutes to evenly disperse the solid particles in the composite polymer solution, fully reacted at 60°C for 4 hours, dried at 20°C, crushed and ground to obtain an aminated solid porous medium capable of heat transfer and energy storage; 1200 parts of high-water sludge containing perfluorinated compounds are uniformly mixed with 2 parts of charcoal particles and 30 parts of solid porous media capable of heat transfer and energy storage to obtain a mixture; wherein the high-water sludge contains 200 micrograms of perfluorinated compounds per 1 kilogram of dry weight of the sludge.

[0030] The mixture was placed in a smoldering furnace, and the bottom mixture was continuously heated at 220°C. At the same time, air was supplied from the bottom of the furnace upward at a speed of 4.0 cm / s, and the mixture was stirred until the mixture reached 450°C and the mixture began to self-sustaining smoldering combustion. The heating and stirring were stopped, and the reaction was continued for 24 hours to obtain a degraded sludge mixture, and the mixture was tested; collecting the waste gas from the mixture produced during the smoldering combustion process; and finally treating the waste gas as well as treating the evaporated waste gas in the mixture.

[0031] The degraded sludge mixture was tested and found to contain 0.01 micrograms of PFOS, or 10 ppt, and 0.06 micrograms of PFOA, or 60 ppt.

[0032] In Comparative Example 1, no polymer solution was used as the matrix, and equal amounts of graphene oxide of hyperbranched polyamide-amine and nano-mica particles were directly used as the solid porous medium, and the rest was the same as in Example 2; In Comparative Example 2, no polymer solution was used as the matrix, and equal amounts of graphene oxide and natural mica particles were directly used as the solid porous medium, and the rest was the same as in Example 2; Comparative Example 3: The solid porous medium is ordinary sand of the same particle size, and stirring is not stopped during the smoldering process. Other aspects are the same as those of Example 2; Comparative Example 4: the solid porous medium is ordinary sand of the same particle size, stirring is stopped during the smoldering process, and the rest is the same as in Example 2; Experimental effect comparison data 1. Monitoring and recording of each temperature point of the smoldering furnace When heating and stirring are stopped, the temperature of different parts inside the smoldering furnace is measured and monitored. A multi-point temperature measurement system inside the smoldering furnace based on wireless data transmission is used. The system uses a single-chip microcomputer as the controller component and an external temperature sensor. Figure 1 The settings of the AE collection points are as follows, and the temperature of each point is recorded, see Table 1; As can be seen from Table 1, in Examples 2-4, because of the introduction of an aminated solid porous medium containing a polymer material grafted with an amine group, which is a heat transfer and energy storage type, the temperature collection points of the smoldering furnace do not fluctuate much over time without providing an external heat source. After 8 hours, it is basically maintained between 800 and 1000°C, and the temperature changes with time, first slightly rising and then falling back. This is mainly because after the external heat source stops heating, the heat at the bottom has not been completely absorbed. The network structure formed with the solid porous medium as the skeleton and the polymer as the vein allows the heat to be quickly conducted and dissipated, and the temperature continues to rise. As the heat is dissipated, the heat in the smoldering furnace is continuously transferred, and the temperature difference will be continuously leveled, causing the temperature to drop slightly again. When there is no external heat source to provide heat, the mica begins to release the stored heat. At the same time, the high molecular polymer is under the action of high temperature, and the carbon-hydrogen bonds are continuously broken, releasing a large amount of heat, which allows the temperature to continue to rise, forming a balance. In Comparative Example 2, because no heat transfer and energy storage type amino-based solid porous medium was introduced and no high molecular polymer was used to increase the heat source, the heat in the smoldering furnace could not be promptly and effectively transferred to various positions of the smoldering furnace. As a result, when there was no external heat source to provide energy, the temperature inside the smoldering furnace dropped sharply and could not provide energy to maintain self-sustaining combustion.

[0033] It can also be seen from the temperature change record table of each temperature collection point AF extracted from Table 1 that the temperature changes of each temperature point in Examples 2-3 are not large, and the temperature of each sampling point in the entire smoldering furnace is very stable. In Comparative Examples 2-3, because the heat transfer of water-containing sludge is slow, the sampling points near the bottom of the smoldering furnace have experienced a rapid temperature rise to varying degrees, and then a rapid drop. In Example 1, because there are relatively few polymer materials, it cannot generate a large amount of heat to help all areas reach high temperatures. Because of the agglomeration of graphene oxide, the temperature dispersion is uneven, and the temperature of the area with more graphene oxide rises quickly. In Comparative Example 2, due to the agglomeration of graphene oxide, local high temperatures appear, and because there are relatively few energy generation points, high temperatures cannot be continuously generated. Although it can maintain slow self-sustaining smoldering, it cannot reach the temperature point where perfluorinated compounds degrade. In Comparative Example 2, because there are fewer available energy sources and the natural mica has little energy storage effect, the energy supply of the entire system is insufficient, the temperature cannot continue to rise, and the temperature difference at each collection point is large. In Comparative Examples 3 and 4, because there are fewer heat sources and no materials can store energy, after heating is stopped, only local areas can continue to absorb heat and generate energy for self-sustaining combustion, maintaining smoldering for 2-3 hours, and then the temperature will drop sharply, ending the entire reaction.

[0034] Table 1, temperature record table of each temperature collection point (℃)

[0035] 2. Determination of thermal conductivity of mixture In the study of the temperature field change over time in the smoldering furnace, the thermophysical parameters are of great significance. Since the smoldering furnace itself is a dynamic equilibrium system, affected by temperature, heat source and material, the mixture can be regarded as a porous semi-fluid medium. The size of the pores is a relative concept that has a significant impact on the heat transfer process of the porous medium. If the pores are filled with air, the thermal conductivity will be low, and when the pores are filled with liquid or solid with high thermal conductivity, the thermal conductivity will be large. The larger the thermal conductivity, the faster the heat transfer, which can solve the problem of rapid heat accumulation. The thermal conductivity of each sampling point when the heating is stopped is measured with a YBF-3 thermal conductivity tester, see Table 2. It can be seen from Table 2 that the thermal conductivity of each sampling point in Examples 2-4 is not much different, and the thermal conductivity is significantly improved than that of Comparative Examples 1-4. This is because first of all, Examples 2-4 have a heat transfer and energy storage type solid porous medium. The solid porous medium contains graphene oxide with high thermal conductivity. When the graphene oxide grafted with hyperbranched polyamide-amine is filled in the pores, a grid skeleton is formed in the mixture, connecting the entire smoldering stove into a large mesh system, greatly improving its thermal conductivity system, thereby accelerating heat transfer. In Example 1, because the graphene oxide is not modified, it is unevenly dispersed in the system, resulting in large differences in the data of each sampling point. In Comparative Example 1, there is no high molecular polymer, and the pores are occupied by water; in Comparative Example 2, no amine-grafted heat transfer and energy storage type solid porous medium is introduced, and the solid medium used is ordinary graphene oxide and ordinary mica. Ordinary mica is easy to absorb water, so it has no effect on improving the thermal conductivity. The ordinary sand used in Comparative Examples 3-4 cannot significantly improve the thermal conductivity. The difference is that stirring is added to Comparative Example 3, so the heat transfer coefficients of each collection point are almost the same. Since there is no stirring in Comparative Example 4, the differences in the collected data are relatively large. Therefore, compared with Comparative Examples 1-4, Examples 2-4 can significantly improve the heat transfer efficiency and continuously provide a heat source for the smoldering furnace to maintain a high temperature of more than 800°C, thereby accelerating the propagation and diffusion of heat and at the same time promoting the degradation rate of perfluorinated compounds.

[0036] Table 2 Thermal conductivity of each sampling point in the smoldering furnace (W / m·K)

[0037] 3. Removal efficiency of perfluorinated compounds Three equal portions of the degraded sludge mixture samples obtained in Examples 1-4 and Comparative Examples 1-4 were taken, two of which were extracted with 2 volumes of methanol and then measured for residual PFOA content and PFOS content by high performance liquid chromatography (HPLC), and the remaining portion was filtered and the generated F ion content was measured by ion chromatography (IC), and the degradation rate and defluorination rate were calculated based on this, as shown in Table 3. It can be seen from Table 3 that the degradation rate and defluorination rate of Examples 2-4 are significantly improved compared with Comparative Examples 1-4. This is because Examples 2-4 provide an aminated solid porous medium grafted with amine groups for heat transfer and energy storage. The aminated solid porous medium can selectively select perfluoro compounds, and then, after adsorbing perfluoro compounds, the high molecular polymer contained therein can generate a temperature that destroys perfluoro compounds during the self-sustaining smoldering combustion process, and can cooperate with auxiliary fuels to reach a temperature for degradation of perfluoro compounds, and can reach a high temperature of more than 800°C, so that the CF bond is completely broken. Although Example 1 can sustain self-sustaining smoldering for a long time, the high temperature time is short, so the degradation efficiency is not high; while Comparative Examples 1-4 have less energy supply for self-sustaining smoldering and cannot sustain smoldering, resulting in poor removal efficiency, and cannot generate high temperatures to destroy the CF bonds. Figure 1 It can also be clearly seen that the removal efficiency of Examples 2 and 3 is significantly improved compared with Comparative Example 1.

[0038] Table 3 Removal rate of perfluorinated compounds

[0039] The above description is only used to illustrate the technical solution of the present invention rather than to limit it. Any equal modifications and changes made to the technical solution of the present invention by ordinary persons in the art, as long as they do not deviate from the overall concept of the present invention, are still within the scope of the present invention.

Claims

1. A method for efficiently smoldering degradation of perfluorinated compounds in sludge, It is characterized in that The method is to put the mixture obtained by mixing sludge, auxiliary fuel and solid porous medium evenly into a smoldering furnace to smolder and burn, so as to degrade and remove perfluorinated compounds; The sludge is a high-water sludge containing perfluorinated compounds, and the content of perfluorinated compounds is 100-300 micrograms per 1 kg of dry weight of the sludge; the auxiliary fuel is one or a mixture of sawdust, rice husk, charcoal particles or crushed straw; The solid porous medium is a solid porous medium capable of heat transfer and energy storage, and its average particle size is less than or equal to 0.5 mm; graphene oxide and nano-mica particles are added to a polyvinyl alcohol solution, stirred for 30 to 50 minutes, so that the solid particles are evenly dispersed in the polyvinyl alcohol solution, fully reacted at 80° C. for 4 hours, and the product is dried at 20° C., crushed and ground to obtain a solid porous medium capable of heat transfer and energy storage; The solid porous medium is an improved solid porous medium capable of heat transfer and energy storage, and is an aminated solid porous medium capable of heat transfer and energy storage grafted with amine groups; The mass ratio of the highly water-containing sludge containing perfluorinated compounds, the auxiliary fuel and the solid porous medium capable of heat transfer and energy storage is 1000-1500:2-4:30-50.

2. The method for efficiently smoldering degradation of perfluorinated compounds in sludge according to claim 1, It is characterized in that The method for preparing the solid porous medium capable of heat transfer and energy storage is specifically as follows: S001, taking natural mica particles and heating them to 600°C for 1 hour to obtain activated mica particles, soaking and stirring the activated mica particles in a concentrated hydrochloric acid solution for 2 to 3 hours, filtering, washing with 70°C deionized water until neutral, and evaporating at 70°C, adding sodium dodecyl sulfate, heating to 80°C, reacting for 2 to 3 hours, centrifuging the obtained solid, washing with 80°C deionized water, evaporating at 80°C, and grinding to obtain nano mica particles with enlarged micropores; wherein the mass ratio of activated mica flakes to sodium dodecyl sulfate is 2:1; S002, high molecular weight polyvinyl alcohol and deionized water are stirred and heated at 100°C for 80 to 120 minutes until the polyvinyl alcohol solution is completely dissolved, and the concentration of the polyvinyl alcohol solution is 3 to 6%; S003, adding graphene oxide and nano-mica particles to a polyvinyl alcohol solution, stirring for 30 to 50 minutes to evenly disperse the solid particles in the polyvinyl alcohol solution, fully reacting at 80°C for 4 hours, drying the product at 20°C, crushing and grinding to obtain a solid porous medium capable of heat transfer and energy storage, wherein the mass ratio of graphene oxide, nano-mica particles and polyvinyl alcohol is 5 to 8:5 to 10:3 to 6.

3. The method for efficiently smoldering degradation of perfluorinated compounds in sludge according to claim 1, It is characterized in that The preparation method of the aminated solid porous medium capable of heat transfer and energy storage is specifically as follows: S101, adding hyperbranched polyamide-amine to an aqueous solution of graphene oxide, adjusting the solution to be alkaline with a 0.05% mass concentration of NaOH solution, then adding 1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, stirring and reacting at 60-80° C. for 20-24 hours, centrifuging, washing with water, and drying to obtain graphene oxide grafted with hyperbranched polyamide-amine; The mass ratio of graphene oxide, 1-ethyl-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and hyperbranched polyamide-amine is 1:1:3-5; S102, high molecular weight polyether ether alcohol and N, N-dimethylamide are stirred and heated at 80°C for 80 to 120 minutes until they are completely dissolved to form a transparent liquid; polylactic acid and ethanol are dissolved in a mass ratio of 1:2 and then added into the transparent liquid to finally obtain a polymer solution; the mass ratio of polyether ether alcohol and N, N-dimethylamide is 1:1; the mass ratio of polylactic acid and polyether ether alcohol is 1:1 to 2; S103, adding graphene oxide grafted with hyperbranched polyamide-amine and nano-mica particles into the polymer solution, stirring for 30 to 50 minutes to evenly disperse the solid particles into the composite polymer solution, reacting at 80° C. for 4 hours, drying the product at 20° C., crushing and grinding to obtain an aminated solid porous medium capable of heat transfer and energy storage.

4. The method for efficiently smoldering degradation of perfluorinated compounds in sludge according to claim 1, It is characterized in that The method for efficiently smoldering and degrading perfluorinated compounds in sludge is specifically as follows: S201, mixing high-water sludge containing perfluorinated compounds, auxiliary fuel and a solid porous medium capable of heat transfer and energy storage to obtain a mixture; S202, putting the mixture into a smoldering furnace, continuously heating the mixture at 220°C to 300°C at the bottom of the smoldering furnace, and supplying air from the bottom of the furnace upward at a speed of 4.0 cm / s to 6.0 cm / s, stirring the mixture until the temperature reaches 400°C to 500°C and the mixture begins to self-sustaining smoldering combustion, stopping heating and stirring, and continuing the reaction for 18 to 24 hours to obtain a degraded sludge mixture, and testing the degraded sludge mixture; S203, collecting waste gas from the mixture generated during the smoldering combustion process; and finally treating the waste gas and the waste gas evaporated from the mixture; S204, sampling and testing the degraded sludge mixture obtained in step S202, if the detected perfluoroalkane concentration does not exceed 50ppt, the reaction is terminated; if it exceeds, continue to heat the degraded sludge mixture to 300°C at the bottom of the smoldering furnace, heat for 1 to 3 hours, supply air from the bottom of the furnace upward at a speed of 4.0cm / s to 6.0cm / s, stop heating, continue the reaction for 4 to 6 hours, retest, if it exceeds, repeat steps S203 and S204 until the detected perfluoroalkane concentration does not exceed 100ppt.

5. The method for efficiently smoldering degradation of perfluorinated compounds in sludge according to claim 1, It is characterized in that Perfluorinated compounds include perfluorooctanoic acid and perfluorooctane sulfonic acid.

6. The method for efficiently smoldering degradation of perfluorinated compounds in sludge according to claim 1, It is characterized in that The particle size of the auxiliary fuel is less than or equal to 0.05 mm, and the average particle size of the solid porous medium is less than or equal to 0.5 mm.

Citation Information

Patent Citations

  • A method for promoting the biodegradation of perfluorinated compounds in sludge

    CN104496141B

  • Thermally conductive flame retardant polymer compositions and uses thereof

    CN104854180A

  • Composite carbon heat source and preparation method thereof

    CN108451027A

  • System and method for thermal destruction of undesired substances by smoldering combustion

    CN110869140A

  • Organic-inorganic hybrid flame-retardant polylactic acid fabric and preparation method thereof

    CN111549526A